2013
DOI: 10.1007/s11255-013-0624-7
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and serum creatinine as predictors of kidney graft outcome

Abstract: The most reliable predictors of graft outcome were Cys C, sCr and proteinuria. Because Cys C is unavailable in many transplant centers, from the practical point of view, sCr remains the most sensitive predictor of graft outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
8
0
3
Order By: Relevance
“…Overall our findings are consistent with results for cystatin C and B2M observed in nontransplant populations (14)(15)(16)(17)(18)(19)(20)(21) and extend the current literature of the strong risk factor associations of these filtration markers with important outcomes into the kidney transplant population. Few studies have evaluated risk associated with cystatin C and B2M in kidney transplant recipients (22)(23)(24)(25). In small studies (sample size from 79 to 129) higher cystatin C levels were associated with graft loss (24,25) and higher serum B2M levels were also associated with eGFR cr decline at 1 and 2 years follow-up (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall our findings are consistent with results for cystatin C and B2M observed in nontransplant populations (14)(15)(16)(17)(18)(19)(20)(21) and extend the current literature of the strong risk factor associations of these filtration markers with important outcomes into the kidney transplant population. Few studies have evaluated risk associated with cystatin C and B2M in kidney transplant recipients (22)(23)(24)(25). In small studies (sample size from 79 to 129) higher cystatin C levels were associated with graft loss (24,25) and higher serum B2M levels were also associated with eGFR cr decline at 1 and 2 years follow-up (22).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated risk associated with low-molecular-weight serum protein levels in kidney transplant recipients. Prior work suggests that higher B2M is associated with greater eGFR decline 1-2 years posttransplant (22) and that both higher cystatin C and B2M are associated with increased risk of mortality (23) and graft loss (23)(24)(25) in transplant recipients. It is not known, however, whether the potential advantage of the lowmolecular-weight serum protein filtration markers over creatinine for estimating cardiovascular and kidney disease risk associations that have been observed in the nontransplant population are present among transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…Vrijednosti JGF iz serumskog cistatina C su imale bolju korelaciju sa jotalamatom i pratile su promjene JGF koje su se dešavale tokom vremena [17]. Ležaić i saradnici [18] su istraživali da li cistatin C može da bude prediktor odbacivanja bubrežnog grafta. Pored cistatina C, određivan je serumski kreatinin, 24-časovni klirens kreatinina, proteinurija, te izračunavana JGF prema jednačinama za cistatin C i kreatinin.…”
Section: Diskusijaunclassified
“…Period praćenja je bio pet godina. Retultati su pokazali da su cistatin C, ali i serumski kreatinin i proteinurija, dobri prediktori odbacivanja grafta [18]. Određivanjem senzitivnosti i specifičnos-ti primjenjenih metoda u određivanju JGF utvrđeno je da je CKD-EPI jednačina imala najveću senzitivnost i specifičnost, koja je bila izraženija u grupi oboljelih od DM.…”
Section: Diskusijaunclassified
“…Although, some studies showed that CyC and or CyC-based equations predicted both patient mortality and graft outcome better than Crbased eGFR equations [34,84] , others founded that CyC and SCr were equally reliable predictors of graft outcome [85] . Interestingly, very recently, a study examined the extent to which the addition of serum CyC improves GFR estimation and mortality prediction, in comparison to various eGFR equations, in a population of 401 liver transplanted patients.…”
Section: Creatinine-based and Cyc-based Egfr Equations As Predictors mentioning
confidence: 99%